2015
DOI: 10.1103/physrevb.91.075208
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen centers and the conductivity ofIn2O3single crystals

Abstract: 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
2
23
0
3
Order By: Relevance
“…The concentration of recombination centers decreases significantly in the atmosphere of hydrogen. The hydrogen may passivate the defects by incorporating in the zinc and indium vacancies on the surface 3032 . In addition, the oxygen molecules adsorbed on the surface of oxides can form a chemical bond with hydrogen and desorb 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of recombination centers decreases significantly in the atmosphere of hydrogen. The hydrogen may passivate the defects by incorporating in the zinc and indium vacancies on the surface 3032 . In addition, the oxygen molecules adsorbed on the surface of oxides can form a chemical bond with hydrogen and desorb 33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen was proposed to act as a shallow donor in In 2 O 3 and thus to increase the carrier density compared with undoped films. Furthermore, previous studies have suggested that the source of doping is attributed to interstitial hydrogen (H i + ) or substitutional hydrogen (H O + ) rather than to doubly charged oxygen vacancies (V O +2 ). ,, Wu et al reported that in In 2 O 3 :H films that contained both, amorphous and crystalline parts, a higher amount of hydrogen was incorporated in the amorphous region compared to the crystalline region.…”
Section: Discussionmentioning
confidence: 99%
“…[33] A high density of hydrogen impurities have also been found in magnetron sputtering grown IGZO with a concentration of 10 20 cm −3 , [34] hydride vapor phase epitaxy (HVPE) grown Ga 2 O 3 , [33f ] and flux grown In 2 O 3 single crystals. [35] The chemistry of hydrogen in oxide semiconductor is quite complex. [33a,36] Hydrogen can be incorporated as interstitials (H i ) and as substitution at the oxygen sites (H O ), [25g,37] and can be neutral H o (inactive), H + (donor) and H − (acceptor).…”
Section: Hydrogen Impuritiesmentioning
confidence: 99%